1981
DOI: 10.1002/hlca.19810640424
|View full text |Cite
|
Sign up to set email alerts
|

New Triterpenes from the Bark of Western White Pine (Pinus monticola DOUGL.)

Abstract: SummaryEleven new triterpenes with the lanostene-type skeleton were isolated from the benzene extract of western white pine bark. Their structures were determined mainly on the basis of physical and spectral data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The NOESY spectrum showed NOE correlations between H-5 and Me-28α and H-1α; and H-9 and Me-18β and Me-19β, respectively. The configuration of the hydroxyl group at position 24 was established by CD using 2% Eu(dpm) 3 in CCl 4 as the solvent. , The CD spectrum of 3 exhibited a positive Cotton effect curve at 285 nm (Δε −1.34) and 310 nm (Δε +1.21), indicating S -configuration of the hydroxyl group at C-24. Accordingly, 3 was elucidated as 3-oxolanost-9β H -7-en-24 S ,25-diol.…”
Section: Resultsmentioning
confidence: 99%
“…The NOESY spectrum showed NOE correlations between H-5 and Me-28α and H-1α; and H-9 and Me-18β and Me-19β, respectively. The configuration of the hydroxyl group at position 24 was established by CD using 2% Eu(dpm) 3 in CCl 4 as the solvent. , The CD spectrum of 3 exhibited a positive Cotton effect curve at 285 nm (Δε −1.34) and 310 nm (Δε +1.21), indicating S -configuration of the hydroxyl group at C-24. Accordingly, 3 was elucidated as 3-oxolanost-9β H -7-en-24 S ,25-diol.…”
Section: Resultsmentioning
confidence: 99%
“…The above data implied that 3 was a tetracyclic triterpene. Careful analysis of 1D-and 2D-NMR data revealed that compound 3 was very similar to (24S)-3b-methoxy-5a-lanost-9(11)-ene-24,25-diol (4) [9], which was also isolated in this investigation, except for the replacement of a Me group by an Obearing CH 2 group in 3. The HMBCs of Me(27) to the three O-bearing C-atoms (C(24), C(25), and C(26) at d(C) 79.3, 73.9, and 67.7) enabled us to locate the Obearing CH 2 C-atom as C(26) (Fig.…”
Section: Results Andmentioning
confidence: 89%
“…Besides these three new compounds, five known compounds, angustanoic acid D [10], 7,8-epoxy-1(12)-caryophyllen-9b-ol [11], junicedric acid [12], 12-hydroxydehydroabietic acid [13], and (24S)-3b-methoxy-5a-lanost-9(11)-ene-24,25-diol [9] were isolated and identified by means of spectroscopic methods. …”
Section: Results Andmentioning
confidence: 99%
“…This was confirmed by HMBC spectral data (see Supporting Information). The relative configuration of the hydroxy group at C-24 was assigned by comparison of the 1 H-NMR spectrum of 2 with that of the known compound [3]. Thus, 2 was lanost-9(11),25-diene-3b,24b-diol.…”
mentioning
confidence: 99%